Designing Virtual Coaching Solutions - Hannes Schlieter; Kai Gand; Thure Georg Weimann; Emanuel Sandner; Karl Kreiner; Steffen Thoma; Jin Liu; Massimo Caprino; Massimo Corbo; Agnese Seregni; Peppino Tropea; Rocio Del Pino; et al. (Business & Information Systems Engineering, 2024)
Especially older persons are prone to disabilities and chronic diseases. These chronic conditions pose a worldwide challenge, leading to deteriorating health, economic strain, loss of life, and a decline in the quality of life (QoL). Therefore, healthcare institutions seek to enhance their strategies for disease prevention and management to uphold the well-being of the community. This leads to the need to regain independence and improve QoL to properly rehabilitate the patients. Virtual Coaches (VCs) in the form of Embodied Conversational Agents are seen as a relevant digital intervention to support the continuity of care. The paper at hand reports on a Design Science Research project about implementing a VC solution to support older patients' home rehabilitation. The study underpins four pivotal design principles: Adaptivity, Coaching Strategy, Multi-user Interface, and Sustainable Infrastructure. The final artifact was tested with 80 patients which were supported in continuing their inpatient rehabilitation at home by using a VC. The evaluation shows both positive results for usability and acceptance of the intervention for four different use cases and a positive impact on the QoL. Given the comprehensive clinical evaluation, the system represents a safe and appealing solution for ensuring the continuity of medical rehabilitation care and the access to personalized cognitive and motor function treatments.
Keywords: 000; Virtual coaching; Digital health; Rehabilitation care; Design science